Methods and рrinciples managing corporate computer networks - Жуков, И. А.; Савченко, А. С.; Кудзиновская, И. П. (Problems of Informatization and Management, 2010)
Principles and methods of management the networks of regional scale or scale of large corporation are considered with separations in a few regions of country. The model of hierarchical structure is grounded with the decentralized control the autonomous segments of network. The methods of transport of managing and alarm information are considered with the use of protocols of application layer. The recommendations on application of different protocols of management networks depending on setting, type, topology and parameters of autonomous segment are given